2020
DOI: 10.1038/s41598-020-69808-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of kaolin and kaolin/ZnO nanoadsorbents in adsorption studies for tannery wastewater treatment

Abstract: In the present study, comparative studies of kaolin and kaolin/ZnO nanocomposites for the adsorption of Cr(VI), Fe(III), COD, BOD, and chloride from tannery wastewater were investigated. ZnO nanoparticles and kaolin/ZnO nanocomposites were prepared by sol-gel followed by wetimpregnation methods. The prepared adsorbents were characterized using different analytical tools such as X-ray diffraction, Fourier transforms infrared, high-resolution transmission electron microscopy, energy dispersive spectroscopy, sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(45 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…Pb (II) ions have the highest percentage removal due to their high electronegativity of 2.33, followed by Ni ions with 1.91 and Cu with 1.90. The higher the electronegativity, the faster the diffusion and removal efficiency ( Egbosiuba et al., 2020 ; Mustapha et al., 2020 ). Finally, the optimal AF-CHAC dosage for the removal of Pb(II), Cu(II), and Ni(II) ions was 4 g/L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pb (II) ions have the highest percentage removal due to their high electronegativity of 2.33, followed by Ni ions with 1.91 and Cu with 1.90. The higher the electronegativity, the faster the diffusion and removal efficiency ( Egbosiuba et al., 2020 ; Mustapha et al., 2020 ). Finally, the optimal AF-CHAC dosage for the removal of Pb(II), Cu(II), and Ni(II) ions was 4 g/L.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum percentage removal for Pb(II), Cu(II), and Ni(II) ions was 99.66, 96.01, and 92.36 %, respectively and this was observed at an equilibrium time of 60 min. Furthermore, increasing the contact time beyond this point resulted in a percentage removal decrease due to blockage or saturation of the adsorbent active sites and the weakening of the binding force as the sorbate concentration decreases ( Mustapha et al., 2020 ). Similar observation was reported by Fatehi et al.…”
Section: Resultsmentioning
confidence: 99%
“…Kaolin is a mineral of layered phyllosilicate clay and a common compound in soils and sediments [20,21]. Due to its cheapness, availability, and unique chemical and physical properties, this clay has been used in many healthrelated matters such as the food industry, wastewater treatment, and bleeding control [22][23][24]. Even though clay particles have no antibacterial properties, the intercalation of Ag particles on them can kill adsorbed bacteria [25].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these inorganic nanoparticles have been extensively applied as nano-adsorbents in order to remove heavy metal ions from wastewater. This is because of their high surface area, high activity, and enhanced structural stability [14][15][16][17][18][19][20]. For instance, Al-Hobaib et al reported that ZnO nanoparticles enhanced hydrophilic properties of reverse osmosis (RO) PA-TFC membranes.…”
Section: Introductionmentioning
confidence: 99%